Difference in physical fitness of judoka after preparation period - Majdov, L.; Stankovic, N.; Escobar Molina, R.; Stamenkoviæc, S. (FIS communications in Physical Education, Sport and Recreation, 2016)
Background: Judo is Olympic sport with high physical and technical/tactical demands. assesment of training outcomes is necessery if competition success is expected. Objective: The purpose of this study was to evaluate the state of sport specific physical fitness of judokas before and after six week preparation period. Methods: the research was realized on a sample of of 15 members of the University judo and sambo club Kinezis from Ni., who compete in Serbian National league (the highest rank of the national competition). The examines were competitors with minimum 5 years of judo training, average age 22.4 +/- 4.5 years. The physical fitness was assessed by using the Special judo fitness test (SJFT). Results: There was an improvement in the SJFT results (from 13.49 to 13.08) but student t-test for dependent samples didn't show that they are statistically (p=0.062). Conclusion: Authors recommend the training program used in the study. In addition, they recommend Special judo fitness test for assessment of judokas current condition of physical fitness.